DETEKSI LANDMARK CITRA WAJAH DENGAN EXTRAKSI FITUR GABOR ANALISA FUZZY - Lim, Resmana (Jurnal Informatika, 2003)
This paper proposes a method that automatically finds human faces as well as its landmark points in color images based on a fuzzy analysis. The proposed approach first uses color information to detect face candidate regions and then uses a fuzzy analysis of the color, shape, symmetry and interior facial features. A deformable Gabor wavelet graph matching is used to locate the facial landmark points describing the face. The latter allows for size and orientation variation since the search for landmark points allows for affine transformations as well as local deformations of the Gabor wavelet graph. The search is performed using a genetic algorithm that is essential because it effectively searches the solution space. Results based on the proposed method are included to verify the effectiveness of the proposed approach. Abstract in Bahasa Indonesia : Paper ini mengusulkan sebuah metode deteksi wajah beserta dengan titik landmarknya pada citra berwarna menggunakan analisa fuzzy. Proses awal menggunakan informasi warna kulit untuk menseleksi calon-calon obyek lantas dilanjukan dengan analisa fuzzy terhadap warna, bentuk, simetri dan fitur/landmark wajah. Proses lokalisasi landmark wajah menggunakan Gabor wavelet graph matching dengan memaksimalkan kemiripan antara landmark wajah model dengan obyek inputan. Proses maksimalisasi kemiripan ini menggunakan algoritma genetika. Hasil-hasil percobaan ditampilkan untuk memberikan gambaran keberhasilan dari metode yang diusulkan. Kata kunci: lokalisasi landmark wajah, analisa fuzzy, graph matching, algoritma genetika, Gabor wavelet.